Development of high impact toughness offshore engineering steel by yttrium-based rare earth addition. (26th November 2021) - Luo, Diqiang; Yu, Yinhong; Zhang, Zhenming; Sun, Lefei; Feng, Xiaoming; Lai, Chaobin
ABSTRACT: The effect of yttrium-based rare earth on the inclusions and impact toughness of EH36 offshore engineering steel were investigated by scanning electron microscopy, electron backscattered diffraction and electron probe x-ray microanalysis techniques. It was found that impact toughness and isotropy of EH36 were enhanced significantly by rare earth addition. The longitudinal and transverse impact toughness at −60°C were increased by 33.5% and 113.7%, respectively. Moreover, the differences between the longitudinal and transverse textures decrease significantly with the addition of rare earth, the low-temperature impact property isotropy increased by 61.1%. Meanwhile, rare earth can modify elongated irregular MnS inclusions into small spherical regular RE-inclusions. Most of the RE-inclusions are within 3μm in diameter, which account for 97.84% of total inclusions. With the addition of rare earth in EH36 offshore engineering steel, the average effective grain size was reduced by 9.7%.